Filter Loss Reducing Agent Polyanionic Cellulose - Li, Ya-Na (International Journal of Scientific Research and Management (IJSRM), 2025)
Poly anionic cellulose, as an upgraded product of sodium carboxymethyl cellulose, emerged in response to the market's demand for higher application performance of carboxymethyl cellulose. It has extensive applications in the field of oil drilling, and its key technical indicators include degree of substitution, viscosity and fluid loss, etc. At present, the production processes of polyanionic cellulose are divided into multiphase method and homogeneous method, and the multiphase method is generally adopted in industrial production. With the development of oil exploration and the increasing attention people pay to environmental pollution problems, the demand for PAC in the oil drilling industry is growing larger and larger. Therefore, the research on PAC is of great significance.